2018
DOI: 10.1111/coa.12686
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gene copy number changes in head and neck cancer

Abstract: The alterations found in our study supports the contribution of gene amplifications and indicate cooperation between certain oncogenes in the pathogenesis of HNSCC. Correlations between amplification of less familiar genes and known oncogenes warrant further investigation. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 28 publications
3
14
1
1
Order By: Relevance
“…Members of the NET (for NocA, Nlz, Elbow, and TLP-1) family have recently been shown to play important roles in embryonic development and tumour progression [9, 10]. It has been shown that ZNF703 is overexpressed in several types of malignancies, including breast cancer [11], lung cancer [12], gastric cancer [13], colorectal cancer [14] and cholangiocarcinoma [15], and its high expression promotes the progression of these cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Members of the NET (for NocA, Nlz, Elbow, and TLP-1) family have recently been shown to play important roles in embryonic development and tumour progression [9, 10]. It has been shown that ZNF703 is overexpressed in several types of malignancies, including breast cancer [11], lung cancer [12], gastric cancer [13], colorectal cancer [14] and cholangiocarcinoma [15], and its high expression promotes the progression of these cancers.…”
Section: Introductionmentioning
confidence: 99%
“…They also indicated that ZNF703 expression can be induced by CCND1 expression. In our previous study, we identified ZNF703 and CCND1 amplification in 18% and 24% of the HNSCC tumours, respectively . Therefore, in this study to evaluate the effect of gene amplification on mRNA expression and crosstalk between ZNF703 and CCND1 in HNSCC, we analysed the association between the expression rates of these genes in HNSCC tumour samples.…”
Section: Introductionmentioning
confidence: 95%
“…Among the key prognostic markers for survival, epidermal growth factor receptor (EGFR), cyclin D1(CCND1), ERCC1, p16, human papillomavirus (HPV), and B‐cell lymphoma‐extra large (Bcl‐xL)/Bcl‐2, as well as the amplification of genes including EMS1 , FGFR1 , and CCND1 have demonstrated some evidence in clinical trials. Others are slower to advance in clinical development because of unconvincing data and few published studies; for example, acetylcholinesterase(AchE), SNPs of specific genes, glutathione S‐transferase (GST), CD44, amplification of specific genes, hypoxic markers, KLK‐6, and MDA‐7/IL‐24; although, this does not preclude them from future investigations and clinical utility.…”
Section: Biomarkers In Hnscc Tumor Tissuesmentioning
confidence: 99%